Migration in A Globalised World New Research Issues and Prospects - Audebert, Cédric; Doraï, Mohamed Kamel (Amsterdam University Press, 2012)
The last two decades have witnessed sweeping changes in the composition, orientation and dynamics of international migration. While it's no surprise these transformations affect societies of origin and settlement, we still seek to understand how and why they carry with them certain social challenges. Migration in a Globalised World shines a light. Ten chapters astutely present theoretical and empirical insights by experts in the fields of international migration and social cohesion, transnationalisation, the migration-development nexus and the ever-blurring categories of refugee and asylum seeker. With its broad thematic scope and lively dialogue between French, Anglo-Saxon and Northern European academic traditions, this volume offers a major new perspective to further research and, potentially, to improve the quality of life in a globalised world.